Investigation of Audit Committee Roles Towards Indonesian Hotel Companies’ Sustainability - Agung, Chris Petra; Inawati, Wahdan Arum (Jurnal Akuntansi, 2025)
Purpose – This study examines the relationship between 1) audit committee and sustainability report (SR) disclosure, 2) SR disclosure and profitability, and 3) audit committee and profitability in hotel companies listed in the hotel, resort, and cruise industry classification of the Indonesia Stock Exchange during 2021-2023 period. Design/methodology/approach – This research is quantitative, and data will be collected from the financial reports and SR of each sample company during the observation year. The data will then be processed, and hypothesis testing will be carried out using Partial Least Squares-Structural Equation Modeling (PLS-SEM) through SmartPLS Version 3 software. Findings – The audit committee positively and significantly affects SR disclosure but does not affect profitability. Profitability is also not affected by SR disclosure. This finding fills the research gap, namely the interaction among the audit committee, SR disclosure and profitability, especially in the context of Indonesian hotel companies. Research limitations/implications – This research involves a fairly limited number of samples and years of observation; however, the results encourage hotel company management to discuss sustainability issues more comprehensively during audit committee meetings so that the depth and breadth of SR disclosure may increase. Keywords: Audit Committee, Profitability, Sustainability Disclosure